Penerapan Asas Keadilan dalam Penetapan Warisan Tanpa Ahli Waris di Peradilan Agama - Najma, Siti Najla Nur; Surahmad Surahmad (JURNAL USM LAW REVIEW, 2025)
This study examines the application of the principle of justice in determining inheritance without heirs in the Religious Court Decision of Tigaraksa Number 291/Pdt.P/2023/PA.Tgrs and its conformity with the Compilation of Islamic Law (KHI). The research is motivated by the lack of uniform interpretation of Article 191 of the KHI in religious court practices, which may result in legal uncertainty and the absence of substantive justice. This study employs a normative juridical method using statutory, case, and conceptual approaches by analyzing the Compilation of Islamic Law, Presidential Instruction Number 1 of 1991, and judicial legal reasoning. The findings indicate that the judges applied the principle of justice substantively and contextually by prioritizing family welfare and the values of maqāṣid al-sharī‘ah, particularly the protection of property (ḥifẓ al-māl) and family ties (ḥifẓ al-nasl). The court interpreted Article 191 of the KHI progressively, concluding that the case did not constitute inheritance without heirs since lawful blood relatives were still present. The novelty of this study lies in its analysis of voluntary inheritance determinations integrating substantive justice, judicial ijtihad (ijtihad qadhā’i), and social welfare considerations. This study recommends that the Supreme Court issue guidelines or circular letters to standardize the interpretation of Article 191 of the KHI in order to ensure legal certainty and consistent application of substantive justice within religious courts.   Penelitian ini bertujuan untuk menganalisis penerapan asas keadilan dalam penetapan harta warisan tanpa ahli waris pada Penetapan Pengadilan Agama Tigaraksa Nomor 291/Pdt.P/2023/PA.Tgrs serta kesesuaiannya dengan Kompilasi Hukum Islam (KHI). Latar belakang penelitian ini didasarkan pada belum seragamnya penafsiran Pasal 191 KHI dalam praktik peradilan agama, yang berpotensi menimbulkan ketidakpastian hukum dan ketidakadilan substantif. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual, melalui analisis KHI, Instruksi Presiden Nomor 1 Tahun 1991, serta pertimbangan hukum majelis hakim. Hasil penelitian menunjukkan bahwa hakim menerapkan asas keadilan secara substantif dan kontekstual dengan mengutamakan kemaslahatan keluarga serta prinsip maqāṣid al-syarī‘ah, khususnya perlindungan terhadap harta (ḥifẓ al-māl) dan silaturahmi keluarga (ḥifẓ al-nasl). Hakim menafsirkan Pasal 191 KHI secara progresif dengan menilai bahwa perkara tersebut tidak termasuk kategori warisan tanpa ahli waris karena masih terdapat kerabat sedarah yang sah. Kebaruan penelitian ini terletak pada analisis penetapan voluntair waris yang mengintegrasikan asas keadilan substantif, ijtihad qadhā’i, serta perspektif kemaslahatan sosial. Penelitian ini merekomendasikan perlunya pedoman atau Surat Edaran Mahkamah Agung guna menyeragamkan penerapan Pasal 191 KHI agar tercipta kepastian hukum dan keadilan substantif di lingkungan peradilan agama.